Nivel de Motivación de los empleados del Comisariato San Rafael del Cantón Caluma - Castro Santos, Jesus del Carmen (2019)
The behavior of people within the work environment depends on multiple factors, in certain occasions the reasons that motivate a person to have a low motivation is due to the environment where they are, for this reason administrative management is a very important process because is present in all areas of the company, and through it you can achieve business goals, and above all promote the personal development of the members of the organization